2017
DOI: 10.3906/sag-1509-26
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood glucose levels and cardiovascular risk in the Spanish Mediterranean population

Abstract: Background/aim: Diabetes is associated with an increased prevalence of cardiovascular disease. Impaired fasting glucose (IFG) is an intermediate clinical situation between normal glucose levels and type 2 diabetes. The aim of this study is to determine how fasting glucose concentrations affect different cardiovascular risk scales. Materials and methods:A descriptive study was conducted with 59,041 Mediterranean Spanish workers. IFG was determined using the American Diabetes Association (ADA) and the World Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
0
2
0
1
Order By: Relevance
“…In addition, based on the previous experience of other authors with Mediterranean populations from Spain [22], we related the items that compose the FINDRISC test and its cutoff points with factors that predispose the presence or increase in CR. It was highly significant when the test scores were grouped dichotomously between high and low risk to be related to HT, T2DM, obesity, and CR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, based on the previous experience of other authors with Mediterranean populations from Spain [22], we related the items that compose the FINDRISC test and its cutoff points with factors that predispose the presence or increase in CR. It was highly significant when the test scores were grouped dichotomously between high and low risk to be related to HT, T2DM, obesity, and CR.…”
Section: Discussionmentioning
confidence: 99%
“…We found that hypertension was correlated with increased risk for prediabetes, which was consistent with previous studies ( 14 , 45 ). For the aspect of dyslipidemia, a Spanish study reported the association of TC, LDL-c, and TG with IFG ( 48 ). A study of Mexican-Americans detected that HDL-c and TG were related to prediabetes, and no associations were found in TC and LDL-c ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…), így erre is fokozott figyelemmel kell lenni. López-Gonzalez és munkatársai például azt találták, hogy az általuk vizsgált közel 60 000 spanyol munkás között azok, akiknél IFG igazolódott nagyobb volt a különböző CV-rizikóbecslő rendszerrel (REGICOR, SCORE) számított CV kockázata a normoglykaemiásokhoz képest (17), Martinez-Larrad és munkatársai pedig IGT esetében bizonyították ezt egy közel 4000 fős, véletlenszerűen kiválasztott kohortban (18). Kérdés, hogy az inzulinrezisztenciának milyen szerepe van az ateroszklerózis és így a fokozott CV-kockázat kialakulásában.…”
Section: Prediabétesz éS a Kardiovaszkuláris Megbetegedések Kockázataunclassified